Laminar burning velocity measurement of CH4/H2/NH3-air premixed flames at high mixture temperatures. (1st January 2023) - Berwal, Pragya; Shawnam,; Kumar, Sudarshan
Highlights: Laminar burning velocity of CH4 /H2 /NH3 -air flames measured at elevated temperatures. Temperature exponent, α remains constant for different ammonia concentration. NH3 addition reduces burning velocity with increased consumption of H, OH radical. Reaction pathway elucidates the role HNO conversion to NO for high NH3 addition. Abstract: The development of carbon-free fuels is essential for establishing sustainable energy growth with ultra-low carbon emissions. In this quest, development of newer fuels with efficient combustion characteristics equivalent to hydrocarbon fuels needs to be encouraged. With this consideration, the present work aims at the measurement of laminar burning velocity of CH4 /H2 /NH3 -air mixture at higher temperatures using the externally heated diverging channel technique. The volume fraction of ammonia is varied from 0 to 30 % by volume in a 4:1 ratio CH4 :H2 fuel blend. The proposed CH4 /H2 /NH3 mixture is analogous to CH4 -air mixture in terms of burning velocity and adiabatic flame temperature. The measurements are obtained for elevated mixture temperature (300–750 K) and equivalence ratio range of ϕ = 0.7–1.2. The measured burning velocities of CH4 /H2 /NH3 mixtures are nearly similar to CH4 -air mixtures for mixture temperatures >550 K. Temperature exponent remains nearly constant irrespective of the NH3 mole-fraction. Predictions of Okafor and Li kinetic-models compare well with the present experimental measurements up to 750 K, whereas Shrestha mechanism over-predicts the burning velocity values. The burning velocity is observed to decrease with an increase in NH3 mole-fraction due to the presence of nitroxyl radical. The present work ably demonstrates the application of CH4 /H2 /NH3 -air mixtures as an efficient alternative to achieve the reduction in carbon-emission targets and develop efficient combustion systems for these derived fuels.